Non Cirrhotic Portal Vein Thrombosis: Diagnostic and Therapeutic Challenge - Syifa Mustika; Pratista Adi Krisna (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Portal vein thrombosis (PVT), the second most common cause of portal hypertension, can be found in cirrhosis and non-cirrhosis patients. Various factors can cause non-cirrhosis PVT, such as biliary infection. Upper gastrointestinal bleeding without sign of liver failure, must be considered as non-cirrhosis PVT manifestation. Combining physical, laboratory, endoscopic and radiological examination is needed to establish the diagnosis of PVT. The principle of PVT management consists of 3 keypoints. They are prevention and treatment of gastrointestinal bleeding, prevention of recurrent thrombosis and portal cholangiopathy therapy. Many aspect should be considered regarding the administration of anticoagulants in PVT patients, especially chronic PVT with cavernomas.